Über Anschauung und reines Bewusstsein. Ein Gesprächsangebot an Thomas Metzinger - Viertbauer, Klaus (Zeitschrift für Theologie und Philosophie, 2026)
Thomas Metzinger identifies a contrast between religion and spirituality to show that spiritual practices such as meditation can lead to experiences of selflessness. In doing so, he offers two arguments: First, he seeks to render his naturalistic self-model theory more plausible by integrating spiritual practice. Second, he presents religion as a carrier of non-naturalistic concepts of the ego and the self and devalues religion as pre-scientific. Metzinger’s distinction is based on the premise that religion must be interpreted as theism and science as naturalism. The present article critically examines this equation of religion with theism and demonstrates, using Friedrich Schleiermacher’s concept of "Anschauung", that spirituality can also be understood within the framework of religious interpretation.